(3cJGH jYbhH Hf GSMGb GdcfOj aj GdUfGYI GdYXejs - (3CHh YeQ GdcfOj , CHh jYbhH Hf eMeO Hf ESMGb GdcfOj, GdcfOj,J (B355 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3HYO GdHSedI bGd jYbhH Hf GSMGb GdcfOj cJH jYbhH Edj GHfI CMeO aj GdUfGYI GdYXej GdJj CNP ef MO QSeI ef GdjhfGfjjf, GdcJGH GdehShe Gdj HWdjehS GdbdhPj GdeSej GdeLSWj s
(3BNQgG (B:s
(3hjMOgG GdNWhW GdChdj CbWGH Gdadcjjf s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3fSNJ ef fSgI SbjeI ZjQ eYJeO YdjgGs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B148 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B142s
Keywords: (3eJaQbGJs